Menganalisis Keefektifan Pembelajaran Bahasa Indonesia melalui Video Interaktif untuk Meningkatkan Motivasi dan Prestasi Belajar Siswa di SMA 6 Padang - Grisma Yuli Arta; Putri Wulandari; Dina Fitria Handayani (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2024)
The aim of this research is to analyze the effectiveness of interactive learning media in the form of interactive videos in increasing the motivation to learn Indonesian at SMA 6 Padang students. This research uses the classroom action method (PTK) with a quantitative and qualitative approach. The method used is a data collection method involving SMA 6 students as samples. The instruments used were questionnaires to measure learning motivation, and tests for Indonesian language learning achievement. The research results showed that each score from the distributed questionnaire reached 93%, which shows that the use of learning media in the form of interactive videos is very effective in increasing learning motivation and learning achievement in SMA 6 Padang students.